1987
DOI: 10.1143/jjap.26.l541
|View full text |Cite
|
Sign up to set email alerts
|

ZnS:Mn Thin Film Electroluminescent Devices Having Doubly-Stacked Insulating Layers

Abstract: ZnS:Mn thin film electroluminescent devices having doubly-stacked insulating layers have been developed. The insulating layer consists of electron-beam evaporated Ta2O5, and rf-magnetron sputtered SiO2 stacked layers. It is concluded that the thick semi-insulating Ta2O5 films (1000 nm) deposited on both sides of the ZnS:Mn active layer act as a carrier injctor for electroluminescence and the thin insulating SiO2 films (80 nm) inserted between the electrodes and Ta2O5 films act as a carrier limiter. The breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Doped zinc sulphide (ZnS) has been the subject of a large number of investigations because of its practical application as a luminophor (Czajka and Gordon 1983;Renz and Schulz 1983;Warren et al 1983;Choudhary et a1"1984; Maheshwari and Pathak 1984;Chaubey and Tripathi 1985;Brada 1989). Attempts were therefore made to increase its efficiency and improve the breakdown voltage margin (Okamoto et al 1979;Ogura et al 1986;Okamoto and Hamakawa i986;Mita et al 1987;Milind et al 1990). It has been reported that even a small amount of impurities such as Fe, Co and Ni present in the phosphor can greatly hamper the luminescence efficiency or can completely destroy it.…”
Section: Introductionmentioning
confidence: 99%
“…Doped zinc sulphide (ZnS) has been the subject of a large number of investigations because of its practical application as a luminophor (Czajka and Gordon 1983;Renz and Schulz 1983;Warren et al 1983;Choudhary et a1"1984; Maheshwari and Pathak 1984;Chaubey and Tripathi 1985;Brada 1989). Attempts were therefore made to increase its efficiency and improve the breakdown voltage margin (Okamoto et al 1979;Ogura et al 1986;Okamoto and Hamakawa i986;Mita et al 1987;Milind et al 1990). It has been reported that even a small amount of impurities such as Fe, Co and Ni present in the phosphor can greatly hamper the luminescence efficiency or can completely destroy it.…”
Section: Introductionmentioning
confidence: 99%
“…22) The prepared Ta 2 O 5 layer had many O vacancies contributing electron conduction, so it could also be expected to act as an electron injection layer. 23) Al thin film was formed on the Ta 2 O 5 layer by thermal evaporation as a cathode. A conventional DC-EL device without an a-Si:H layer was also prepared for comparison.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[1][2][3] Furthermore, these films have also been used for insulating films for electroluminescent ͑EL͒ display devices. 4,5 In the EL devices, the insulating films are required to be prepared on transparent electrodes such as indium tin oxide ͑ITO͒ electrodes. Therefore, the electrical properties of the Ta 2 O 5 films on the ITO electrodes play an important role in improving the performances of the EL devices.…”
Section: Electrical Properties Of Ta-sn-o Films On Indium Tin Oxide Ementioning
confidence: 99%